The synthesis of N-substituted 4-fluoro-1,8-naphthalimides - Nadiia F. Fedko; Valeriy F. Anikin; Vira V. Veduta (Журнал органічної та фармацевтичної хімії, 2022)
Aim. To synthesize 4-fluoro-1,8-naphthalic acid imide and its derivatives substituted in the imide ring. Results and discussion. 4-Fluoro-1,8-naphthalimide was obtained using acenaphthene as the starting material. N-alkyl-4-fluoro-1,8-naphthalimides were synthesized via the phase transfer catalytic alkylation of 4-fluoro-1,8-naphthalimide with haloalkanes. Imidation of 4-fluoro-1,8-naphthalic anhydride with aminoacids resulted in the formation of N-carboxyalkyl-1,8-naphthalimides. These substances can be considered as potential fluorescent labels capable of binding to amino groups of various biological molecules as they contain carboxylic functionality in their structure. Experimental part. The structure of the compounds synthesized was confirmed by FT-IR, 1H NMR and 13C NMR spectroscopy, and mass-spectrometry. Conclusions. It has been shown that 4-fluoro-1,8-naphthalinedicarboxylic acid imide can be obtained following the synthetic route “acenaphthene – 5-fluoroacenaphthene – 4-fluoro-1,8-naphthalic anhydride – 4-fluoro-1,8-naphthalimide”. 4-Fluoro-1,8-naphthalimide can be alkylated by butyl iodide and octyl bromide using tetraalkylammonium salts as a phase transfer catalyst resulted in N-butyl-4-fluoro-1,8-naphthalimide and N-octyl-4-fluoro-1,8-naphthalimide. As a result, N-carboxyalkyl-4-fluoro-1,8-naphthalimides have been obtained for the first time by aminolysis of 4-fluoro-1,8-naphthalic anhydride with glycine, β-alanine and 6-aminocaproic acid.